Information for Management Decision Making - Simanauskas, Leonas; Skyrius, Rimvydas (Ekonomika, 1996)
The article deals with information requirements for business decisions and the relations between information features and decision quality. A certain type of information system, decision support systems (DSS), emersed in developed countries in the late seventies, as an answer to the unsatisfied information requirements of the middle and upper management. At present, the developing and postcommunist countries on their way to market economy are experiencing the growing demand for information technology to support business initiative and decision-making. This leads to the increased importance of computerized decision-support methods. The unstructured nature of the majority of business decisions, coupled with a turbulent and unstable business environment in Eastern European countries, brings rut a number of contradictions and specific problems. One important problematic area is decision-information acquisition and usage. The decision-information can roughly be split into internal and external information for the organization. The internal information comes from the resources of the organization’s traditional information system and is available either immediately or through simple conversion procedures. It is important to note that the information resources of the organization provide a lot of additional data, facts, and conclusions that can be extracted or drawn from the often neglected internal information vaults. External information plays an exclusive role in managerial decision-making, mainly because of the potential to reduce uncertainty in important decisions. Therefore, the ability to tap the external information resources is vital for a decision-support system, and its importance can be supported by the proliferation of public databases and other independent providers of information services. Some issues of the information usage for managerial decision-making ar discussed, namely, variety and relative importance of information sources, information acceptability and relevance, information richness, and rational and irrational ways of using the information. Considering the importance of external information, the article also gives attention to the technical, organizational, and managerial issues of creating, managing and running public databases in Lithuania, given their importance to the infrastructure of business activities and especially to the sector of intellectual services, including information services.